1998
DOI: 10.1007/s002400050054
|View full text |Cite
|
Sign up to set email alerts
|

Expression of gonadotropin-releasing hormone (GnRH) and GnRH receptor mRNA in prostate cancer cells and effect of GnRH on the proliferation of prostate cancer cells

Abstract: The purpose of this study was to determine the production of gonadotropin-releasing hormone (GnRH), the co-occurrence of GnRH receptors in prostate cancer cells, and the effect of GnRH on prostate cancer cell proliferation. Four human prostate cancer cell lines were studied. LNCaP is an androgen sensitive prostate cancer cell line, DU-145 and PC-3 are androgen resistant, and TSU-Pr1 is uncharacterized. The expression of GnRH and GnRH receptor mRNAs were assessed by in situ hybridization and the effect of exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 16 publications
2
23
1
Order By: Relevance
“…This is in apparent contradiction of earlier work showing direct inhibition of PC3 cell proliferation by GnRH analogues (Limonta et al 1992, Palyi et al 1999 but is in accord with the lack of endogenous receptor binding and signalling (data herein) and with previous work showing no inhibition of proliferation (Bahk et al 1998). The reasons for such discrepancies are unknown but could relate to culture conditions, particularly since these have been shown to cause selection of functionally distinct sub-populations of PC3 cells (Festuccia et al 2000).…”
contrasting
confidence: 98%
See 1 more Smart Citation
“…This is in apparent contradiction of earlier work showing direct inhibition of PC3 cell proliferation by GnRH analogues (Limonta et al 1992, Palyi et al 1999 but is in accord with the lack of endogenous receptor binding and signalling (data herein) and with previous work showing no inhibition of proliferation (Bahk et al 1998). The reasons for such discrepancies are unknown but could relate to culture conditions, particularly since these have been shown to cause selection of functionally distinct sub-populations of PC3 cells (Festuccia et al 2000).…”
contrasting
confidence: 98%
“…However, GnRH receptors (GnRH-Rs) (often along with GnRH) may also be expressed in these cancers (Miller et al 1985, Emons & Schally 1994, Emons et al 1996, Schally 1999, Schally et al 2001. Interest in these receptors stems primarily from the fact that GnRH analogues (or cytotoxic derivatives thereof ) can inhibit proliferation of cell lines derived from such cancers, implying that such direct effects may contribute to the efficacy of GnRH analogues in cancer therapy (Miller et al 1985, Qayum et al 1990, Limonta et al 1992, Dondi et al 1994, Emons & Schally 1994, Emons et al 1997, Bahk et al 1998, Palyi et al 1999, Schally 1999, Halmos et al 2000, Ravenna et al 2000, Schally et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…This is a very important consideration in the design and synthesis of targeted anticancer agents. To confirm the activity of the conjugate, we further tested its efficacy in LNCaP, a hormonedependent cell line, and PC-3, a hormone-independent cell line, two cell lines overexpressing the LHRH-R (38). Our antiproliferative studies showed that the deslorelin-docetaxel conjugate is significantly more cytotoxic in both cell lines compared with docetaxel alone.…”
Section: Discussionmentioning
confidence: 97%
“…However, there is increasing evidence showing that the effects of GnRH-a on carcinoma of the prostate are mediated not only through suppression of gonadal steroids, but also through a direct effect on cell growth (33)(34)(35)(36). This effect may indicate that besides its effect on androgen-sensitive carcinoma of the prostate, GnRH-a may be efficient also in the treatment of hormonerefractory prostate cancer.…”
Section: Discussionmentioning
confidence: 99%